Isolation, Identification and Sensitivity Test of Staphylococcus aureus against Amoxicillin of the Milk sample in the Mastitis Crossbred Ettawa Goat at Girimulyo Area, Kulon Progo, Yogyakarta - Amalia Krishna Dewi (Jurnal Sain Veteriner, 2013)
Staphylococcus aureus is the main bacteria causing mastitis of the Ettawa crossbreed goat. The mastitis causes significant economic losses due to decreasing of milk production. Mastitis in goat could threat the survival rate of her kids because decrease in quality and quantity of milk products. The toxin produced by S.aureus can also cause the death of their mothers. The present research is aimed to isolate and identify S. aureus from mastitis milk sample of Ettawa crossbreed goat, and does its sensitivity to amoxicillin as well. The milk samples were collected from the mastitis crossbreed Ettawa goat at Girimulyo area, Kulonprogo, Yogyakarta. In the present study, 20 milk samples of Ettawa crossbreed goat were used to isolate and identify S. aureus based on the culture, Gram staining, biochemical and sugar tests. The isolates then tested for their sensitivity to amoxicillin. Nine isolates in the present study identified as S. aureus in which they grew on MSA, formed round cells cluster, Gram +, fermented manitol, lactose and maltose. They coagulated the rabbit plasma and reacted positively to the clumping factor and Voges Proskouer test. Based on the results of the sensitivity test to 10 ìg amoxicillin is known that 8 isolates (88,89%) are sensitive to amoxicillin. Therefore, it can be concluded that there are 9 isolates from 20 mastitis milk samples of Ettawa crossbreed goat identified as S. aureus. Staphylococcus aureus isolates are mostly sensitive to amoxicillin.